Friends of the Family in the Cofigurative and Prefigurative Culture Behaviours - Ferenz, Krystyna (Pedagogika, 2013)
Opening the political borders triggered cultural diffusion in the European countries as the open communicative space accelerated the pace of globalization processes. As a result, changes occurring within a society influence the lives of fundamental social groups, i.e. the families. The last decades in Poland have marked a period of intense changes in the everyday life culture, and the examples of the persons coming from three generations reflect the significance of prefigurative and cofigurative cultures.